Peningkatan Kesadaran Masyarakat terhadap Konservasi Laguna Segara Anakan melalui Sistem Vertikal dan Horizontal Aquaponik - Endang Hilmi; Lilik Kartika Sari; Tri Nur Cahyo; Norman Arie Prayogo; Teuku Junaidi; Arif Mahdiana (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2023)
The lagoon conservation in Segara Anakan is developed to reduce tidal flooding, abrasion, water pollution and tsunami disaster. Vertical and horizontal akuaponik system aims to reduce impact of water permanent inundation in mangrove conservation area. The socialization of mangrove conservation aimed to teach and give information of mangrove conservation, rehabilitation model using vertical and horizontal aquaponic and the planning bioploc in mangrove area. This activity used the focus group discussion and demonstration plot. The results of this activity were socialization of  socio-economic factors to support mangrove and coastal management, Oceanographic factors of mangrove and coastal management, Mangrove rehabilitation using aquaponic vertical and horizontal systems, Improvement of water quality in catfish cultivation with biofloc system, the conservation of mangrove ecosystem, and analysis of main stakeholder to support lagoon conservation.